Method and device for testing load deformation temperature of resin matrix composite material

CN120820425BActive Publication Date: 2026-10-27AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510967384.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2026-10-27
Estimated Expiration
2045-07-14

AI Technical Summary

Technical Problem

目前,通常通过油浴法、静态热机械法等对复合材料进行负荷变形温度测试;然而,油浴法能达到的最高温度有限,无法满足树脂基复合材料所需的负荷变形温度;静态热机械法能够提供的载荷较小,若通过减小试样尺寸适应载荷,会使得测试结果与实际温度相差较大,且上述两种方法的测试时间均较长,导致测试过程效率较低

Benefits of technology

[0030]本申请提供的树脂基复合材料负荷变形温度测试方法,首先确定对试样进行负荷变形施加的载荷值F、判断试验进行负荷变形的结束挠度值,基于树脂基复合材料的负荷变形温度高于其玻璃化转变温度Tg的特性,通过两个阶段进行加热,通过加热程序的第一阶段,以v1将测试装置的内部温度加热至Tg,之后再将试样安装进测试装置对应位置,通过加热程序的第二阶段以v2进行持续加热,且v2<v1,并同步开启加载程序对试样施加载荷,直至试样达到结束挠度值,结束测试装置的加载程序与加热程序,获得树脂基复合材料复合变形温度Tf,观察试样,以确保数据的有效性;这样,通过对试样施加所需的载荷值F,确保试样的尺寸结构更接近实际情况,以提高测试的准确性;并通过两个加热阶段,提升第一阶段的加热速率,减少整体测试时间,提高了测试效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120820425B_ABST
    Figure CN120820425B_ABST
Patent Text Reader

Abstract

The application discloses a resin-based composite load deformation temperature testing method, determines a load value F applied to a sample for load deformation, judges an end deflection value of the load deformation test, and based on the characteristic that the load deformation temperature of the resin-based composite is higher than the glass transition temperature T g of the resin-based composite, heats the internal temperature of a testing device to T g by two-stage heating, then installs the sample into a corresponding position of the testing device, continuously heats by the second stage of the heating program at v2, and v2 f is less than v1, simultaneously starts a loading program to apply a load to the sample until the sample reaches the end deflection value, and obtains the load deformation temperature T f of the resin-based composite; in this way, the required load value F is applied to the sample, the size structure of the sample is closer to the actual situation, the testing accuracy is improved, and the heating rate of the first stage is improved by two heating stages, and the testing efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of load deformation temperature technology, and more specifically, to a method and apparatus for testing the load deformation temperature of resin-based composite materials. Background Technology

[0002] Load deformation temperature is an important parameter for measuring the relationship between temperature and deformation of resin-based composite materials, and it is a crucial indicator for evaluating the heat resistance of these materials. Currently, load deformation temperature testing of composite materials is typically conducted using methods such as the oil bath method and the static thermomechanical method. However, the oil bath method has a limited maximum achievable temperature, which cannot meet the required load deformation temperature of resin-based composite materials. The static thermomechanical method can provide relatively small loads, and if the sample size is reduced to accommodate the load, the test results will deviate significantly from the actual temperature. Furthermore, both of these methods are time-consuming, resulting in low testing efficiency.

[0003] In summary, improving the testing efficiency and accuracy of the load deformation temperature of resin-based composite materials is a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0004] In view of this, the purpose of this application is to provide a method and apparatus for testing the load deformation temperature of resin-based composite materials, thereby improving the testing efficiency and accuracy of the load deformation temperature of resin-based composite materials.

[0005] To achieve the above objectives, this application provides the following technical solution:

[0006] A method for testing the load deformation temperature of a resin-based composite material includes: preparing a specimen; determining the load value F required to subject the specimen to load deformation; and determining the deflection value at the end of the load deformation process. Determine the glass transition temperature T of the sample. g Install the resin-based composite material load deformation temperature testing device; initiate the first stage of the heating program of the testing device, heating the internal temperature of the testing device to t1 at a heating rate v1, where t1 = T. g Install the sample into the corresponding position on the testing device; activate the second stage of the testing device's heating program, continuously heating at a heating rate v2, where v2 < v1; activate the first stage of the testing device's loading program, applying an equal acceleration load to the sample until the load value increases to F; activate the second stage of the testing device's loading program, continuously applying a constant load F to the sample until the sample reaches the final deflection value. The loading and heating programs of the testing device were terminated, and the composite deformation temperature T of the resin-based composite material was obtained. f Observe the samples to determine the validity of the data.

[0007] In some embodiments, the characteristic feature is that determining the load value F required to deform the specimen specifically includes: performing a three-point bending test on the specimen, using the formula:

[0008] The load value F required to obtain the load deformation is expressed in N; where σ f The bending stress generated by the applied load value F is expressed in MPa; h is the thickness of the specimen in mm; b is the width of the specimen in mm; and l is the span of the specimen in the bending test in mm.

[0009] In some embodiments, Formula 1 is used: The span l can be obtained, where A is the proportionality coefficient between the span and the sample thickness;

[0010] Using Formula 2: The bending stress σ generated by the applied load value F can be obtained. f , of which E f The bending modulus is obtained from the bending test, which can produce a load-deflection curve of the specimen.

[0011] Flexural modulus E f Formula 3 can be used: The values ​​are obtained as follows: ΔP is the load increment corresponding to the initial straight line segment on the load-deflection curve, in N; Δδ is the deflection increment corresponding to ΔP on the load-deflection curve, in mm.

[0012] Substitute Formula 1, Formula 2, and Formula 3 into the formula ,available:

[0013]

[0014] The thickness h of the sample can be obtained by measurement. It can be obtained from the load-deflection curve; the ratio A of span to thickness can be obtained by observing the failure mode of the bending test.

[0015] In some embodiments, the span-to-thickness ratio factor A is obtained by observing the failure mode of the bending test. Specifically, the failure mode of the bending test is compression failure of the upper surface and tensile failure of the lower surface of the specimen. In resin-based composite materials, when the reinforcing fiber is T300, A is 32; when the reinforcing fiber is T700 or T800, A is 40; when the reinforcing fiber is glass fiber, A is 16.

[0016] In some embodiments, the deflection value at the end of the load deformation process of the specimen is determined. Specifically, this includes using the formula: Obtain the final deflection value of the load deformation process. The unit is mm; where, The initial deflection value of the specimen when the load increases from zero to F during the load deformation test, in mm; This represents the standard deflection value of the specimen, in mm.

[0017] In some embodiments, formula four is used: The standard deflection value of the sample can be obtained. ,in, The bending strain increment is taken as 0.2;

[0018] Substitute Formula 1 and Formula 4 into the formula ,available:

[0019]

[0020] in, Obtained from the load-time curve in the load deformation test.

[0021] In some embodiments, installing a resin-based composite material load deformation temperature testing device specifically includes: setting the distance between the first support and the second support to be l, where l can be accessed via... The ratio A of the span to the thickness can be selected according to the type of reinforcing fiber in the resin-based composite material; the sample thickness h can be measured; the pressure bar is connected to the universal testing machine so that the axis of the pressure bar is vertically downward and the pressure bar is located in the middle position between the first support and the second support, and the coaxiality of the pressure head of the pressure bar with the first support and the second support is kept consistent.

[0022] In some embodiments, initiating the first stage of the testing device heating program, heating the internal temperature of the testing device to t1 at a heating rate v1, specifically includes: initiating the first stage of the testing device heating program, raising the temperature inside the testing device from zero to the glass transition temperature T of the sample at a heating rate of 10°C / min. g Record the highest temperature of the first stage of heating as t1, and keep the first stage at that temperature for at least 2 minutes.

[0023] In some embodiments, installing the sample into the corresponding position of the testing device specifically includes: raising the temperature inside the testing device to T. g In this case, the sample is placed on the first and second supports, such that the length direction of the sample is aligned with the line connecting the first and second supports; the pressure bar is moved downwards, so that the pressure head makes slight contact with the upper surface of the sample.

[0024] In some embodiments, activating the second stage of the testing device heating program, and continuously heating at a heating rate v2, specifically includes: activating the second stage of the testing device heating program, and increasing the internal temperature of the testing device from T at a heating rate of 6°C / min. g It begins to heat continuously.

[0025] In some embodiments, initiating the first stage of the testing device loading program, applying an equal acceleration load to the sample until the load value increases to F, specifically includes: during the heating process of the second stage of the testing device heating program, initiating the first stage of the testing device loading program, and increasing the load value applied to the sample by the indenter from zero to F at a loading rate of 10 N / min, and recording the deflection value at this time. Then, maintain a constant load value F.

[0026] In some embodiments, a load is applied to the first specimen until the final deflection value is reached. The composite deformation temperature T of the resin-based composite material was obtained. f The first sample test is completed; the testing device is then cooled by air cooling until the internal temperature of the testing device reaches T. g Install the second sample, repeat the second stage of the heating program and the loading program, and conduct cyclic testing.

[0027] In some embodiments, observing the sample to determine the validity of the data specifically includes: observing whether there is obvious delamination after the sample is tested; if there is no obvious delamination, the data is judged to be valid; if there is delamination after the sample is tested, observing whether there are defects in the delamination area; if there are no defects in the delamination area, the data is judged to be valid.

[0028] A resin-based composite material load deformation temperature testing device is applied to the resin-based composite material load deformation temperature testing method described above.

[0029] The testing apparatus includes: a heating chamber for heating the sample; a support fixedly connected inside the heating chamber; a first support and a second support slidably connected to the support to adjust the distance between them; and a pressure rod, the first end of which is connected to a universal testing machine, and the second end of which is provided with a pressure head. The pressure head, the first support, and the second support form a contoured structure, and the pressure head is used to apply a load to the sample.

[0030] The method for testing the load deformation temperature of resin-based composite materials provided in this application first determines the load value F applied to the specimen for load deformation and then determines the deflection value at the end of the load deformation test. The load deformation temperature of resin-based composite materials is higher than their glass transition temperature T.g The characteristics are achieved through a two-stage heating process. In the first stage of the heating procedure, the internal temperature of the test device is heated to T using v1. g Then, the sample is installed in the corresponding position of the testing device, and continuous heating is performed in the second stage of the heating program at v2, where v2 < v1. At the same time, the loading program is started to apply a load to the sample until the sample reaches the final deflection value. The loading and heating programs of the testing device were terminated, and the composite deformation temperature T of the resin-based composite material was obtained. f The specimens are observed to ensure the validity of the data; in this way, by applying the required load value F to the specimens, the size and structure of the specimens are made closer to the actual situation, thereby improving the accuracy of the test; and by using two heating stages, the heating rate of the first stage is increased, the overall test time is reduced, and the test efficiency is improved. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of this application. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0032] Figure 1 A schematic flowchart illustrating the method for testing the load deformation temperature of resin-based composite materials provided in this application embodiment;

[0033] Figure 2 The bending load-displacement curve of the composite material provided in the embodiments of this application;

[0034] Figure 3 Heating temperature-time curve provided for embodiments of this application;

[0035] Figure 4 The load-time curve diagram in the load deformation test provided in the embodiments of this application;

[0036] Figure 5 A schematic diagram illustrating the failure modes of a sample provided in an embodiment of this application;

[0037] Figure 6 This is a schematic diagram of the failure defects in the sample provided in the embodiments of this application. Figure 1 ;

[0038] Figure 7 This is a schematic diagram of the failure defects in the sample provided in the embodiments of this application. Figure 2 ;

[0039] Figure 8This is a schematic diagram of the structure of the resin-based composite material load deformation temperature testing device provided in the embodiments of this application.

[0040] Explanation of reference numerals in the attached figures:

[0041] 100-Heating environment chamber, 110-Bracket, 121-First support, 122-Second support, 130-Pressure rod, 131-Pressure head;

[0042] 200-sample. Detailed Implementation

[0043] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0044] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. The terminology used in the following embodiments is for the purpose of describing specific embodiments only and is not intended to be a limitation of this application. As used in the specification and appended claims of this application, the singular expressions "a," "an," "the," "the," "the," and "this" are intended to also include expressions such as "one or more," unless the context clearly indicates otherwise.

[0045] References to "one embodiment" or "some embodiments" as described in this specification mean that one or more embodiments of this application include a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, the phrases "in one embodiment," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiment, but rather mean "one or more, but not all, embodiments," unless otherwise specifically emphasized. The terms "comprising," "including," "having," and variations thereof mean "including but not limited to," unless otherwise specifically emphasized.

[0046] The "multiple" mentioned in the embodiments of this application refers to two or more. It should be noted that in the description of the embodiments of this application, terms such as "first" and "second" are used only for the purpose of distinguishing descriptions and should not be construed as indicating or implying relative importance, nor should they be construed as indicating or implying order.

[0047] The terms "parallel" and "perpendicular" used in this application refer to "basically parallel" and "basically perpendicular" in practical operation. "Basically parallel" can be understood as parallelism with a certain degree of error, and similarly, "basically perpendicular" can be understood as perpendicularity with a certain degree of error.

[0048] Current standards (GB / T1643.1, GB1643 / T.2, GB / T1634.3) specify an oil bath method for load deformation testing of rubber, plastics, and thermosetting laminates, with a maximum temperature of only 260℃. However, this method is not suitable for resin-based composite materials with load deformation temperatures reaching 350℃. The oil bath method cannot meet the load deformation temperature requirements of resin-based composite materials, and its low heating rate results in excessively long heating times, leading to prolonged testing time and low testing efficiency.

[0049] In existing technologies, static thermomechanical methods are also used to test the load deformation temperature of composite materials. However, the maximum load of static thermomechanical methods is only 30N, which cannot meet the load requirements of high-strength and high-toughness resin-based composite materials. If the sample size is reduced to reduce the applied load, the internal stress distribution will be changed due to the small sample size, and the number of layers will be too small, resulting in a large error between the test results and the actual results. In addition, the heating time is too long, resulting in low test efficiency.

[0050] Therefore, this application provides a method and apparatus for testing the load deformation temperature of resin-based composite materials, thereby improving the testing efficiency and accuracy of the load deformation temperature of resin-based composite materials.

[0051] like Figure 1 As shown in the embodiments of this application, a method for testing the load deformation temperature of a resin-based composite material includes:

[0052] S100, Sample preparation

[0053] Multiple specimens are prepared for the test process. The specimens used in the bending test and load deformation test mentioned later are of the same size, that is, the layup, width and thickness of all specimens are the same, to ensure the validity of the data.

[0054] S200. Determine the load value F required to deform the specimen.

[0055] S210. Perform a three-point bending test on the specimen.

[0056] It should be noted that the three-point bending test involves supporting both ends of the specimen along its length with supports and applying a load to the middle of the specimen.

[0057] Using the formula: The load value F required to obtain the load deformation can be obtained, in N; where σ fThe bending stress generated by the applied load value F is expressed in MPa; h is the thickness of the specimen in mm; b is the width of the specimen in mm; and l is the span of the specimen in the bending test in mm.

[0058] S220. To obtain the load value F, use Formula 1: The span l can be obtained, where A is the proportionality coefficient between the span and the sample thickness.

[0059] Using Formula 2: The bending stress σ generated by the applied load value F can be obtained. f , of which E f To determine the flexural modulus of the resin-based composite material through a bending test, the bending test yields a load-deflection curve of the specimen, as shown in the figure below. Figure 2 As shown.

[0060] Flexural modulus E f Formula 3 can be used: The values ​​are obtained as follows: ΔP is the load increment corresponding to the initial straight line segment on the load-deflection curve, in N; Δδ is the deflection increment corresponding to ΔP on the load-deflection curve, in mm.

[0061] Substitute Formula 1, Formula 2, and Formula 3 into the formula ,available:

[0062]

[0063] The thickness h of the sample can be obtained by measurement. It is possible Figure 2 The load-deflection curves shown are obtained; the span-to-thickness ratio factor A is obtained by observing the failure modes of the bending test.

[0064] S230. Observe the specimen after the bending test. The bending failure mode is the compression of the upper surface and the tension of the lower surface of the specimen. This is a reasonable bending failure. If the specimen experiences upper surface compression and delamination failure after the bending test, the ratio factor A of the span and thickness should be increased.

[0065] Specifically, for resin-based composite materials with reinforcing fibers, the recommended value of A can be selected according to the type of reinforcing fiber: when the reinforcing fiber is T300, A is 32; when the reinforcing fiber is T700 or T800, A is 40; when the reinforcing fiber is glass fiber, A is 16.

[0066] In reality, there are many different types of fibers, such as T1100, which has higher strength. Different ratio coefficients A can be selected according to different types of fibers. This application does not limit this.

[0067] In this way, by measuring the thickness h of the sample and selecting the corresponding ratio coefficient A between the span and the thickness, the load value F that needs to be applied to the sample for load deformation can be determined. Furthermore, since the load value F can meet the requirements of the resin-based composite material sample, and the sample size is consistent in the bending test and the load deformation test, the accuracy of the load deformation temperature test is improved, making the test results closer to the actual situation.

[0068] S300. Determine the final deflection value of the specimen during the load deformation process.

[0069] S310. Using the formula: Obtain the final deflection value of the load deformation process. The unit is mm; where, The initial deflection value of the specimen when the load increases from zero to F during the load deformation test, in mm; This represents the standard deflection value of the specimen, in mm.

[0070] S320. Obtain the standard deflection value of the specimen.

[0071] Using Formula 4: The standard deflection value of the sample can be obtained. ,in, The value represents the bending strain increment, taken as 0.2, in units of %.

[0072] S330. Substitute Formula 1 and Formula 4 into... ,available:

[0073]

[0074] The ratio A between the span and the thickness is determined in S230, and the thickness h of the specimen can be measured. During the load deformation test, the following can be obtained: Figure 4 The load-time curve shown can be obtained through... Figure 4 Obtain the initial deflection value .

[0075] S400, Determine the glass transition temperature T of the sample. g

[0076] The glass transition temperature T of resin-based composite materials can be determined by consulting or testing. g It can be determined by methods such as dynamic mechanical analysis, differential scanning calorimetry, and thermomechanical analysis, but the embodiments of this application do not limit this.

[0077] S500, Installation of Resin-based Composite Material Load Deformation Temperature Testing Device

[0078] Resin-based composite material load deformation temperature testing device, such as Figure 8 As shown.

[0079] S510. Set the distance l between the first support 121 and the second support 122, where l is the span of the sample 200, according to Formula 1 in S220: The distance l between the first support 121 and the second support 122 can be obtained by taking the selected span-to-thickness ratio A and the measured thickness h of the sample 200.

[0080] S520. Connect the first end of the pressure bar 130 to the universal testing machine, and make the axis of the pressure bar 130 vertically downward, so that the pressure bar 130 is located in the middle position between the first support 121 and the second support 122, and keep the coaxiality of the pressure head 131 of the pressure bar 130 basically consistent with the first support 121 and the second support 122, so that the coaxiality is within 0.03mm, to ensure that the position of the pressure head 131 applying load to the sample 200 is accurate, so as to further improve the accuracy of the test data.

[0081] S600, First stage of starting the heating procedure of the test device

[0082] The first stage of the testing equipment heating program is initiated by raising the temperature inside the testing device from zero to the glass transition temperature T of the sample at a heating rate of 10℃ / min. g Record the highest temperature of the first stage of heating as t1, and keep the first stage at that temperature for at least 2 minutes.

[0083] Thus, the load deformation temperature of the resin-based composite material is higher than its glass transition temperature T. g Due to the characteristics of this process, since the sample 200 is not placed in the testing device in the first stage of the heating procedure, the overall heating time is shortened by increasing the heating rate in the first stage. The temperature inside the testing device is first raised to the glass transition temperature T in the first stage of the heating procedure. g This improves overall testing efficiency.

[0084] Meanwhile, since the first support 121, the second support 122, the pressure head 131, etc. in the testing device are all made of metal, the thermal conductivity and thermal expansion of the metal material are different from those of the resin-based composite material. By not placing the sample 200 in the first stage of the heating process, the strain caused by the thermal expansion of the metal material during the heating process is reduced, the impact on the sample 200 is reduced, and the accuracy of the test on the sample 200 is further improved.

[0085] S700. Install the sample into the corresponding position on the testing device.

[0086] The temperature inside the testing device has risen to T. gThen, the sample 200 is placed on the first support 121 and the second support 122, and the length direction of the sample 200 is aligned with the direction of the line connecting the first support 121 and the second support 122, so as to ensure the accuracy of the span l of the sample 200.

[0087] Then, the universal testing machine is started, and the pressure bar 130 is driven to move downward, so that the pressure head 131 makes slight contact with the upper surface of the specimen 200, in order to complete the preparation for the load deformation test of the specimen 200.

[0088] S800, the second stage of starting the heating procedure of the test device.

[0089] After placing the sample 200 into the testing device, the second stage of the heating program is initiated, raising the internal temperature of the testing device from T at a heating rate of 6℃ / min. g It begins to heat continuously.

[0090] S900, the first stage of starting the test device loading program

[0091] Simultaneously with initiating the second stage of the heating program, the first stage of the testing device's loading program was started, with a loading rate of 10 N / min, increasing the load applied by the indenter to the specimen from zero to the load value F. The deflection value at this point was recorded. Then, maintain a constant load value F.

[0092] S1000, Second stage of starting the test device loading program

[0093] A constant load F is continuously applied to the specimen until the specimen reaches the final deflection value. The loading and heating programs of the testing device were terminated, and the load deformation temperature T of the resin-based composite material was obtained. f Thus, the load deformation temperature T of the first tested specimen was obtained. f .

[0094] The testing device was cooled by air cooling until the internal temperature of the testing device dropped to T. g Install the second sample, repeat the second stage of the heating program and the loading program, and conduct cyclic testing.

[0095] S1100. Observe the sample and determine the validity of the data.

[0096] First, observe whether there is obvious stratification after testing sample 200, such as Figure 5 The image shows a case where sample 200 exhibits obvious delamination, including delamination at the edges and in the middle. If no delamination is observed in sample 200, the data is considered valid.

[0097] If delamination is present in sample 200, use a magnifying glass or optical microscope with a magnification of less than 50x to examine the defects in the delamination area, such as... Figures 6-7 As shown, if there are such in the layered region Figures 6-7 If the indicated resin-rich defect is found, the data is invalid; if no corresponding defect exists, the data is considered valid.

[0098] In this way, by further evaluating the tested sample 200 to ensure the validity of the data, the accuracy of the test is further improved.

[0099] The method for testing the load deformation temperature of resin-based composite materials provided in this application first determines the load value F applied to the sample for load deformation and then determines the deflection value at the end of the load deformation test. The load deformation temperature of resin-based composite materials is higher than their glass transition temperature T. g The characteristics are achieved through a two-stage heating process. In the first stage of the heating procedure, the internal temperature of the test device is heated to T using v1. g Then, the sample is installed in the corresponding position of the testing device, and continuous heating is performed in the second stage of the heating program at v2, where v2 < v1. At the same time, the loading program is started to apply a load to the sample until the sample reaches the final deflection value. The loading and heating programs of the testing device were terminated, and the composite deformation temperature T of the resin-based composite material was obtained. f The specimens are observed to ensure the validity of the data; in this way, by applying the required load value F to the specimens, the size and structure of the specimens are made closer to the actual situation, thereby improving the accuracy of the test; and by using two heating stages, the heating rate of the first stage is increased, the overall test time is reduced, and the test efficiency is improved.

[0100] This application also provides a resin-based composite material load deformation temperature testing device, which is applied to the above-mentioned resin-based composite material load deformation temperature testing method.

[0101] like Figure 8 As shown, the testing device includes a heating environment chamber 100, which is used to heat the sample 200. It is understood that the heating environment chamber 100 has a heating module and a module for monitoring and feeding back the real-time temperature, which will not be described in detail here.

[0102] A bracket 110 is fixedly connected inside the heating environment chamber 100. A first support 121 and a second support 122 are slidably connected to the bracket 110. The first support 121 and the second support 122 are damped slidingly connected to the bracket 110, so that the first support 121 and the second support 122 can be fixed in the corresponding adjusted positions to ensure stability during the testing of the sample 200.

[0103] A pressure rod 130 is slidably connected to the top of the heating environment chamber 100, so that the first end of the pressure rod 130 is connected to a universal testing machine, and the universal testing machine drives the pressure rod 130 to move. A pressure head 131 is provided at the second end of the pressure rod 130 to apply a load to the sample 200, such as... Figure 2 As shown, the indenter 131, the first support 121, and the second support 122 are contoured structures to ensure that the coaxiality between the indenter 131, the first support 121, and the second support 122 is consistent, thereby ensuring the accuracy of the position where the load is applied to the sample 200 and further improving the accuracy of the test of the sample 200.

[0104] In practice, it also includes a control system, which connects the universal testing machine and the heating environment chamber 100. The universal testing machine is controlled to apply load through the control system, and the heating temperature of the heating environment chamber 100 is controlled through the control system to realize the load deformation test of the sample 200.

[0105] The above description of the disclosed embodiments enables those skilled in the art to make or use this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for testing the load deformation temperature of resin-based composite materials, characterized in that, include: Prepare samples; Determine the load value F that needs to be applied to deform the specimen; Determine the final deflection value of the specimen during the load deformation process. ; Determine the glass transition temperature T of the sample g ; Install a load deformation temperature testing device for resin-based composite materials; The first stage of the heating program for the testing device is initiated, heating the internal temperature of the testing device to t1 at a heating rate v1, where t1 = T. g ; Install the sample into the corresponding position on the testing device; The second stage of the heating program of the test device is started, and continuous heating is carried out at a heating rate of v2, where v2 < v1; In the first stage of starting the loading program of the testing device, an equal acceleration load is applied to the sample until the load value increases to F; The second stage of the testing device loading program is initiated, in which a constant load F is continuously applied to the specimen until the specimen reaches the final deflection value. The loading and heating programs of the testing device were terminated, and the load deformation temperature T of the resin-based composite material was obtained. f ; Observe the samples to determine the validity of the data; The determination of the final deflection value of the specimen during the load deformation process is described. Specifically, it includes: Using the formula: Obtain the final deflection value of the load deformation process. The unit is mm; where, The initial deflection value of the specimen when the load increases from zero to F during the load deformation test, in mm; This represents the standard deflection value of the specimen, in mm.

2. The method for testing the load deformation temperature of resin-based composite materials according to claim 1, characterized in that, Determining the load value F required to deform the specimen includes: A three-point bending test was performed on the specimen, using the formula: The load value F required to obtain the load deformation is expressed in N; where σ f The bending stress generated by the applied load value F is expressed in MPa; h is the thickness of the specimen in mm; b is the width of the specimen in mm; and l is the span of the specimen in the bending test in mm.

3. The method for testing the load deformation temperature of resin-based composite materials according to claim 2, characterized in that, Using Formula 1: The span l can be obtained, where A is the proportionality coefficient between the span and the sample thickness; Using Formula 2: The bending stress σ generated by the applied load value F can be obtained. f E f The bending modulus is obtained from the bending test, which can produce a load-deflection curve of the specimen. Flexural modulus E f Formula 3 can be used: The values ​​are obtained as follows: ΔP is the load increment corresponding to the initial straight line segment on the load-deflection curve, in N; Δδ is the deflection increment corresponding to ΔP on the load-deflection curve, in mm. Substitute Formula 1, Formula 2, and Formula 3 into the formula ,available: The thickness h of the sample can be obtained by measurement. This can be obtained from the load-deflection curve; By observing the failure modes of bending tests, the proportionality coefficient A between span and thickness is obtained.

4. The method for testing the load deformation temperature of resin-based composite materials according to claim 3, characterized in that, By observing the failure modes of bending tests, the proportionality coefficient A between span and thickness is obtained, specifically including: The failure mode of the bending test is compression failure of the upper surface and tensile failure of the lower surface of the specimen; In resin-based composite materials, when the reinforcing fiber is T300, A is 32; when the reinforcing fiber is T700 or T800, A is 40; and when the reinforcing fiber is glass fiber, A is 16.

5. The method for testing the load deformation temperature of resin-based composite materials according to claim 4, characterized in that, Using Formula 4: The standard deflection value of the sample can be obtained. ,in, The bending strain increment is taken as 0.2; Substitute Formula 1 and Formula 4 into the formula ,available: in, Obtained from the load-time curve in the load deformation test.

6. The method for testing the load deformation temperature of resin-based composite materials according to claim 4, characterized in that, Install a load deformation temperature testing device for resin-based composite materials, specifically including: Let the distance between the first support and the second support be l, where l can be reached by... The ratio A of the span to the thickness can be selected according to the type of reinforcing fiber in the resin-based composite material; the sample thickness h can be measured. Connect the pressure bar to the universal testing machine so that the axis of the pressure bar is vertically downward and the pressure bar is located in the middle position between the first support and the second support, keeping the pressure head of the pressure bar coaxial with the first support and the second support.

7. The method for testing the load deformation temperature of resin-based composite materials according to claim 6, characterized in that, The first stage of the testing device heating program is initiated, heating the internal temperature of the testing device to t1 at a heating rate v1, specifically including: The first stage of the heating program for the testing device is initiated, raising the temperature inside the device from zero to the glass transition temperature T of the sample at a heating rate of 10℃ / min. g Record the highest temperature of the first stage of heating as t1, and keep the first stage at that temperature for at least 2 minutes.

8. The method for testing the load deformation temperature of resin-based composite materials according to claim 7, characterized in that, Install the sample into the corresponding position on the testing device, specifically including: The temperature inside the testing device was raised to T. g In this case, the sample is placed on the first support and the second support, such that the length direction of the sample is consistent with the direction of the line connecting the first support and the second support. The pressure bar moves downward, causing the indenter to make slight contact with the upper surface of the sample.

9. The method for testing the load deformation temperature of resin-based composite materials according to claim 8, characterized in that, The second stage of the testing device's heating program is initiated, with continuous heating at a heating rate of v2, specifically including: The second stage of the heating program for the testing device is initiated, raising the internal temperature of the testing device from T at a heating rate of 6℃ / min. g It begins to heat continuously.

10. The method for testing the load deformation temperature of resin-based composite materials according to claim 9, characterized in that, The first stage of initiating the testing device loading program involves applying an equal acceleration load to the sample until the load value increases to F, specifically including: During the second stage of the heating process of the testing device, the first stage of the loading process of the testing device is started, with a loading rate of 10 N / min, so that the load value applied by the indenter to the sample increases from zero to F, and the deflection value at this time is recorded. Then, maintain a constant load value F.

11. The method for testing the load deformation temperature of resin-based composite materials according to claim 10, characterized in that, The first specimen was subjected to a load until the final deflection value was reached. The composite deformation temperature T of the resin-based composite material was obtained. f The testing of the first sample is now complete; The testing device was cooled by air cooling until the internal temperature of the testing device dropped to T. g Install the second sample, repeat the second stage of the heating program and the loading program, and conduct cyclic testing.

12. The method for testing the load deformation temperature of resin-based composite materials according to claim 1, characterized in that, Observe the samples to determine the validity of the data, specifically including: Observe whether there is obvious stratification after the sample is tested. If there is no obvious stratification, the data is considered valid. If delamination occurs after sample testing, observe whether there are defects in the delamination area. If there are no defects in the delamination area, the data is considered valid.

Citation Information

Patent Citations

  • Bending deflection test device for high temperature vacuum environment

    CN106679914A